Unionized Part-Time Professionnals and Opportunities for Filling Full-Time Vacancies and Training - Zeytinoglu, Isik (Relations industrielles / Industrial Relations, 1992)
This study analyzes the factors that might influence career opportunities for unionized part-time professionals in comparison to their full-time counterparts. The results suggest that employers' less favourable perceptions of part-time professionals, the differences in career goals and interests of full-time and part-time professionals, and the constraints that operate in collective agreements or lack of collective agreement clauses, all influence part-time professionals' career opportunities. These three factors lead to differences in filing full-time vacancies and training for equally qualified professionals who perform the same job but are in full-time and part-time schedules